Principles of Environmental Legislation in UN, EU and Republic of Serbia - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
A key turning point regarding to environmental protection was the United Nations Conference on the Human environment held in Stockholm, in1972. On the Conference was adopted the UN Declaration on the Human environment. On that occasion established fundamental principles of environmental protection. At the Conference, UNEP, held in Rio de Janeiro in 1992. has adopted the UN Declaration on the Environmental protection and sustainable development.. The Council of Europe has adopted a number of documents in which the central part is the protection of the environment. The Council of Europe adopted the following conventions: Convention on the Conservation of European Wildlife and Natural habitats in 1979; Convention on Civil Liability for Damage Resulting from Activities Dangerous to the Environment in 1993; Convention on the protection of Environment trough Criminal Law, in 1998; and European Lanscape Convention in 2000. The Constitution of Republic of Serbia proclaims the right to a healthy environment, but also establishes the obligation of all, to conserve and improve it. The fundamental principles of environmental protection system in our county are regulated by the following .The Law on Environmental Protection, The Law on Environment Impact, The Law on Environment Strategic Impact and The Law on Integrated Pollution Prevention and Control. These Laws are aimed towards establishing an environmental management system and providing protection from natural balance degradation. With a great number of Laws in particular sectors of environmental protection, Republic of Serbia received modern legislation, which formed, a good basis for economic and social activities involved in environmental protection.